On Structural Features Necessary for Near‐IR‐Light Photocatalysts. Issue 39 (28th July 2015) - Wang, Gang; Huang, Baibiao; Li, Zhujie; Wang, Zeyan; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Whangbo, Myung‐Hwan
Abstract In the search for photocatalysts that can directly utilize near‐IR (NIR) light, we investigated three oxides Cu3(OH)4SO4 (antlerite), Cu4(OH)6SO4, and Cu2(OH)3Cl by photodecomposing 2, 4‐dichlorophenol over them under NIR irradiation and by comparing their electronic structures with that of the known NIR photocatalyst Cu2(OH)PO4. Both Cu3(OH)4SO4 and Cu4(OH)6SO4 are NIR photocatalysts, but Cu2(OH)3Cl is not. Thus, in addition to the presence of two different CuOm and Cu′On polyhedra linked with CuOCu′ bridges, the presence of acceptor groups (e.g., SO4, PO4) linked to the metal oxygen polyhedra is necessary for NIR photocatalysts.